2018
DOI: 10.1111/irv.12539
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and molecular characterization of influenza viruses in Burkina Faso, sub‐Saharan Africa

Abstract: BackgroundThe importance of influenza viruses in respiratory infections in sub‐Saharan Africa has been historically overlooked, including in Burkina Faso.ObjectivesThis study therefore aimed at evaluating the prevalence and seasonal occurrence of influenza viruses in children under 5 years old, at risk of influenza‐related complications, presenting with influenza‐like illness (ILI) or severe acute respiratory infection (SARI). The study also aimed at identifying the periods with increased influenza transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 38 publications
1
17
1
Order By: Relevance
“…The two sequences collected in 2014 belonged to clade 6C represented by A/Dakar/02/2014 while all sequences collected between 2015 and 2016 belonged to clade 6B represented by A/South Africa/3626/2013. Several other studies have shown the same temporal circulation of these two clades [22, 23] while others showed the presence of viruses of clade 6B in the 2014 season [2426]. The 2014 virus strains differed from the vaccine strain by acquiring an amino acid substitution on antigenic site Ca (K142R).…”
Section: Discussionmentioning
confidence: 99%
“…The two sequences collected in 2014 belonged to clade 6C represented by A/Dakar/02/2014 while all sequences collected between 2015 and 2016 belonged to clade 6B represented by A/South Africa/3626/2013. Several other studies have shown the same temporal circulation of these two clades [22, 23] while others showed the presence of viruses of clade 6B in the 2014 season [2426]. The 2014 virus strains differed from the vaccine strain by acquiring an amino acid substitution on antigenic site Ca (K142R).…”
Section: Discussionmentioning
confidence: 99%
“…In Burkina Faso, a country in the semiarid Sahel and Savanna zones of West Africa, malaria transmission remains high, with marked seasonality in the rainy season [9e11]. Influenza virus has been reported to circulate in Burkina Faso [12,13], but its importance and that of other viral respiratory infections in the aetiology of nonmalaria fever remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, seven cases of the SARI were due to IAV infection, five were because of IBV infection, two were due to the A(H1N1)pdm09 virus, and another five were due to the H3N2 virus infection. This study reported that different types and strains of influenza viruses were responsible for inflicting ILI and SARI among children in Burkina Faso [93].…”
Section: Burkina Fasomentioning
confidence: 85%